A Quality Improvement Project to Reduce Postcesarean Opioid Consumption. Issue 4 (July 2021) - Kahn, Kristien Marie; Demarco, Kathleen; Pavsic, Joy; Sangillo, Julie
Abstract: Background: The opioid epidemic is a public health emergency in the United States, stemming in part from widespread misuse and overprescribing of opioids following surgery. Approximately 1 in 300 women with no prior exposure to opioids develops an opioid use disorder following cesarean birth. Effective management of postcesarean pain requires individualized treatment and a balance of the woman's goals for optimal recovery and ability to safely care for her newborn. The American College of Obstetricians and Gynecologists recommends a multimodal approach to pain management after cesarean birth. Methods: In April 2019, a multidisciplinary team was formed at New York University Langone Health to study opioid use postcesarean. The team used the Plan, Do, Study, Act process model for continuous quality improvement to launch a postcesarean pathway called "Your Plan After Cesarean, " a standardized visual tool with quantifiable milestones. It facilitates integration of women's preferences in their postcesarean care, and emphasizes providers' routine use of nonpharmacological interventions to manage pain. Results: During the pilot period of the project, postcesarean high consumption of 55 to 120 mg of opioids was reduced from 25% to 8%. By January 2020, 75% of women postoperative cesarean took little-to-no opioids during their hospital stay. By February 2021, the total number of opioids consumed by women after cesarean birth in-hospital was reduced by 79%. Satisfaction among women with pain management after cesarean continued to be high. Clinical Implications: Reduction in postcesarean opioid administration and the number of opioids prescribed at hospital discharge can be accomplished without having a negative effect on women's perceptions of post-op pain relief. These changes can potentially be a factor in helping to avoid an opioid-naive woman who has a cesarean birth from developing an opioid use disorder. Abstract : Opioid use reduction after cesarean birth has become a common initiative in hospitals in the United States to minimize risk of opioid naïve women developing a substance use disorder after surgery. In this quality improvement project, decreased use of opioids post-operatively in the hospital and after discharge was accomplished by a multidisciplinary team working in collaboration with women who gave birth via cesarean. Patient satisfaction with pain relief management remained high after the project was introduced.